Phytoplankton and Bacterial Responses to Monsoon-Driven Water Masses Mixing in the Kuroshio Off the East Coast of Taiwan - Lai, Chao-Chen; Wu, Chau-Ron; Chuang, Chia-Ying; Tai, Jen-Hua; Lee, Kuo-Yuan; Kuo, Hsiang-Yi; Shiah, Fuh-Kwo (Frontiers in Marine Science, 2021)
Biogeochemical responses to mixing were examined in two cruise surveys along a transect across the Kuroshio Current (KC) in May and July 2020. Two stations located at the South China Sea (SCS)–KC mixing and the KC waters were chosen for the diel study. In the euphotic zone ( 100 m depth), the average values of nitrate (0.97–1.62 μM), chlorophyll-a (Chl-a, 0.36–0.40 mg/m3), and primary production (PP; 3.46 ± 1.37 mgC/m3/day) of the mixing water station (MWS) of the two cruises were several folds higher than those of the KC station (KCS; nitrate, 0.03–0.10 μM; Chl-a, 0.14–0.24 mg/m3; and PP, 0.91 ± 0.47 mgC/m3/day). In the July cruise, the maximal bacterial production (BP) at the MWS (3.31 mgC/m3/day) was 82% higher in comparison with that of the KCS (1.82 mgC/m3/day); and the readings of Chl-a showed no trend with BP in the oligotrophic KCS, but a positive relationship was found among these measurements at the mesotrophic MWS. This implies that the trophic status of the system might affect phytoplankton–bacteria interactions. The backward-trajectory analyses conducted by an observation-validated three-dimensional model identified that the prevailing southwest monsoon drove a northeastward “intrusion” of the SCS waters in July 2020, resulted in mixing between SCS and Kuroshio (KC) waters off the east coast of southern Taiwan. For the first time, this study demonstrates that the high biological biomass and activities that occur in the KC are induced by the northward intrusion of the SCS waters.